The electron spin and spin magnetic moment in dual-4 d space-time Quantum mechanics (JOURNAL OF ADVANCES IN PHYSICS, 2016)
In dual-four-dimensional space-time quantum mechanics, the spin of micro object is caused by the rotation of field matter sphere itself. In its own frame of reference, the radius is defined as the static Compton momentum R0=Ä§/m0cï¼Œand frequency is Î½0=E0/h. In the Dynamic frame of reference, the radius is defined as the dynamic Compton momentum R1=Ä§/mcï¼Œand frequency is Î½1=E1/h. m0 and m is the static and dynamic mass of a micro matter sphere, respectively. The electron spin s and spin magnetic moment both can be calculated by the field matter sphere model. If the frame of reference is in the complex space-time, and we observe the motion in a Minkowshi Space, then there will be a dual four dimensional complex space-time. The fluctuation motion of field matter is De Broglie matter wave.